A meta-analysis of the efficacy of venlafaxine extended release 75–225 mg/day for the treatment of major depressive disorder. (1st February 2017) - Thase, Michael; Asami, Yuko; Wajsbrot, Dalia; Dorries, Kathleen; Boucher, Matthieu; Pappadopulos, Elizabeth
Abstract: Objective: To evaluate the short-term efficacy of venlafaxine extended release (ER) 75–225 mg/day compared with placebo for treating major depressive disorder (MDD) and to examine associations between baseline characteristics and efficacy outcomes in MDD patients treated with venlafaxine ER 75–225 mg/day. Research design and methods: This meta-analysis included published and unpublished short-term, double-blind, placebo-controlled, Wyeth/Pfizer sponsored studies of venlafaxine ER at doses up to 225 mg/day in adults with MDD. Clinical trial registration: All trials were conducted before trial registration became mandatory. Main outcome measures: Change from baseline in the 17-item Hamilton Rating Scale for Depression (HAM-D17 ) total score was analyzed over time using a mixed-effects model for repeated measures with terms for study, treatment group, visit, interaction between treatment group and visit, and baseline score as a covariate. Associations between baseline demographic and clinical characteristics and the probability of HAM-D17 response and remission at week 8 were evaluated using logistic regression models, with terms for study, treatment group, and baseline characteristics in the models. Safety and tolerability was assessed based on adverse events (AEs) and discontinuations due to AEs. Results: The full analysis set included 1087 patients from five studies that fulfilled selection criteria. Statistically significant separation between venlafaxine ER and placebo groups for HAM-D17 total score was seen at week 2 and all subsequent assessments ( p -values <.0001). There was no significant interaction between treatment and baseline HAM-D17 total score. Probability of HAM-D17 remission at week 8 decreased with increasing baseline HAM-D17 total score ( p = .0012; OR: 0.94); however, baseline HAM-D17 total score did not predict response. Discontinuations due to AEs were reported for 9.4% of venlafaxine-ER-treated patients compared with 3.6% of placebo-treated patients. Key limitations: Five studies met the criteria for inclusion. Several differences in design between included studies limited the analysis: one study did not include a week 3 assessment (the week 3 time point was therefore dropped from the analysis), one study had two venlafaxine ER dose arms, which were combined into one group for the meta-analysis, and mixed- and flexible-dose studies were pooled. Conclusions: Venlafaxine ER 75–225 mg/day effectively reduced symptoms of depression in patients with MDD overall and in patients with either lower (≤23) or higher (>23) HAM-D17 total score at baseline.